2020
DOI: 10.3892/mmr.2020.11492
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib sensitizes chemoresistant NSCLC cells to doxetaxel via regulating autophagy and enhances the therapeutic efficacy in advanced and refractory/recurrent NSCLC

Abstract: The prognosis of advanced non-small cell lung cancer (nSclc) is poor; therefore, identifying novel treatment strategies for patients with nSclc is important. The present study aimed to investigate the efficacy of apatinib plus docetaxel vs. docetaxel alone, as well as their effects on regulating autophagy markers in patients with advanced nSclc. Furthermore, it was evaluated whether apatinib sensitized chemoresistant nSclc cells to docetaxel via regulating autophagy. a total of 39 patients with advanced nSclc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Over the past few years, studies have evaluated the efficacy and safety of apatinib alone or apatinib plus paclitaxel/docetaxel versus paclitaxel/docetaxel in the treatment of advanced NSCLC. 7 , 8 However, the results were inconclusive due to the small sample sizes and other mixed factors that affect the treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, studies have evaluated the efficacy and safety of apatinib alone or apatinib plus paclitaxel/docetaxel versus paclitaxel/docetaxel in the treatment of advanced NSCLC. 7 , 8 However, the results were inconclusive due to the small sample sizes and other mixed factors that affect the treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of the AEs, such as diarrhea, decreased appetite, fatigue, and HFS, were mild or moderate and could be tolerated ( 27 , 28 ). Since most of our patients had no specific target, such as EGFR mutation or ALK translocation, the amazing efficiency of this regimen was likely exerted by the reasonable combination of pemetrexed or docetaxel ( 29 ), as the single application of either drug had displayed limited or no efficiency, especially for patients with brain metastasis ( 30 ). Originally, apatinib was regarded as an anti-angiogenesis inhibitor against VEGFR-2, similar to drugs of a similar type, namely, sorafenib, sunitinib, and cabozantinib ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the present study demonstrated that apatinib plus chemotherapy significantly increased the ORR compared with chemotherapy alone in patients with advanced LUAD. The potential reasons for this are as follows: i) Apatinib may inhibit angiogenesis and tumor growth in LUAD, which would help improve treatment response (25-28); and ii) apatinib may have a synergistic effect with chemotherapy by sensitizing LUAD cells to chemotherapy, thereby enhancing the treatment response (15,29). Survival is also prolonged by apatinib plus chemotherapy in patients with advanced NSCLC, according to previous studies (16,23,30).…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib is an orally-administered, small-molecule vascular endothelial growth factor receptor-2 inhibitor that suppresses tumor angiogenesis (13). Recent studies have reported the potential benefit of apatinib plus chemotherapy for the treatment of advanced NSCLC (14)(15)(16). For instance, the overall remission rate has been reported to be improved by apatinib plus chemotherapy vs. chemotherapy alone in patients with advanced NSCLC (37 vs. 10%, respectively) (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation